Hukum Keluarga Islam Di Brunei Darussalam - Arif Sugitanata Arif (Hukum Keluarga Islam IAIN LANGSA, 2021)
This article tries to explain how to reform the field of Islamic family law in Brunei Darussalam while at the same time describing the background and product of family law reform itself. The data used in this study is a qualitative study, then the method used is descriptive-analytical. With conclusions that include, first, family law is a law that has provisions on the territory of family members within the scope of the household which includes certain fields such as marriage, descent, maintenance, hadhanah, guardianship, and inheritance. Second, the background of the birth of Islamic law reform that occurred in this era was caused, among other things, to fill the legal vacuum because the norms contained in the fiqh books did not regulate it, while the legal needs of society continued to grow, the influence of economic globalization and science and technology, the influence of reforms. in various fields that provide opportunities for Islamic law to become a reference in national law, the influence of reforming Islamic legal thought, both by foreign Islamic law experts and national Islamic law experts, especially regarding the development of science and technology as well as gender issues and thirdly, the product of family law reform in Brunei Darussalam is divided into two scopes, namely munakahat and Mawaris, where part of the munakahat itself includes, Marriage Registration, Minimum Age Restriction for Marriage, Role of Marriage Guardian, Polygamy, Divorce, Khulu', Rujuk. Whereas in Mawaris it includes mandatory wills.